The effectiveness and safety of prophylactic central neck dissection in clinically node-negative papillary thyroid carcinoma patients: A meta-analysis - Wang, Yao; Xiao, Yibo; Pan, Yan; Yang, Shuhao; Li, Kainan; Zhao, Wei; Hu, Xulin (Frontiers in Endocrinology, 2023)
Abstract Objective: This meta-analysis was performed to evaluate the effectiveness and safety of prophylactic central neck dissection (PCND) in patients with clinically node-negative (cN0) papillary thyroid carcinoma. Materials and methods: A meta-analysis of the literature was performed using the key words “papillary thyroid carcinomas” and “lymph node ecisions” for searches of electronic databases. Complications such as transient hypocalcemia, permanent hypocalcemia, transient and permanent hypoparathyroidism, transient and permanent vocal cord paralysis, transient recurrent and permanent recurrent laryngeal nerve injury, and local recurrence were pooled by meta-analysis. Stata17.0 was used to carry out the meta-analysis. Results: Data were extracted from 15 studies. In the present review, the group of patients who had total thyroidectomy (TT) with PCND had a lower local recurrence than the group with TT alone (OR 0.22, 95% CI 0.10-0.45, P = 0.000), whereas the incidence of permanent hypocalcemia (OR 4.24, 95% CI 1.05-17.22, P = 0.043) and transient hypoparathyroidism (OR 2.14, 95% CI 1.34-3.42, P =0.001) were higher. No significant differences were recorded in the incidence of other complications: transient hypocalcemia (OR 2.24, 95% CI 0.77-6.51, P = 0.138), permanent hypoparathyroidism (OR 1.70, 95% CI 0.89-3.27, P = 0.111), transient vocal cord paralysis (OR 1.48, 95% CI 0.78-2.83, P = 0.231), permanent vocal cord paralysis (OR 1.44, 95% CI 0.53-3.94, P = 0.477), transient recurrent laryngeal nerve injury (OR 1.47, 95% CI 0.93-2.32, P = 0.102) and permanent recurrent laryngeal nerve injury (OR 1.24, 95% CI 0.56-2.74, P = 0.587) between the two groups. Conclusion: Compared with TT alone, TT with PCND was more effective in reducing local recurrence without increasing the risk of recurrent laryngeal nerve, thyroid and vocal cord, except for hypocalcemia and transient hypoparathyroidism. Keywords: Papillary Thyroid Carcinomas, Lymph Node Excisions, Effectiveness, Safety, Meta-analysis